EFFECT OF GELLING MATRIX COMPOSITION, STORAGE CONDITIONS AND CAPSULE BREAKAGE ON GERMINATION OF ROSA INDICA SYNTHETIC SEEDS - I. Gull; A. Noreen; M. S. Aslam; Z. Abbas1; M. A. Athar (Journal of Animal and Plant Sciences, 2019)
Storage of germplasm using synthetic seed technology is useful to avoid somaclonal variations as well as to cut down the cost and labor of germplasm maintenance under in vitro culturing conditions. In the present study, different parameters that affect the viability and regrowth ability of Rosa indica germplasm stored as synthetic seeds were optimized. The compact, firm, transparent synthetic seeds showing maximum regeneration rate (100 %) were prepared and stored in three different types of air tight storage vessels (glass jars, polypropylene tubes and plastic bags) at 4 °C and 25 °C for various time durations (0-8 weeks). No significant difference in regeneration frequency of Rosa indica synthetic seeds was recorded at different storage conditions. However, the storage temperature significantly influenced the viability and regrowth ability of synthetic seeds. The survival rate (80%) of encapsulated explants was observed up to 8 weeks at 4 °C and declined with elapse of storage duration. Facilitated extrusion of shoot from gel seed and pre-treatment of synthetic seeds with 100 mM KNO3for 5 minutes improved the regeneration frequency while mechanical removal of gel bead resulted in complete loss of explant viability.
Keywords: synthetic seed; viability; Rosa indica; nodal segments